TARI PASIHAN BHONDAN SAYUK SEBUAH MAKNA TEKS - Slamet MD (Institut Seni Indonesia Surakarta, 2006)
Bondhan Sayuk compiled to be inspired by Enggar-Enggar dance which have preexisted. Sunarno as orderer dance conscious Bondhan Sayuk that this dance in the begining fill compiled karawitan song music by Marto Pa ngrawit, what motivat desire have baby. Studying Bondhan Sayuk can be understood if in the theatre of him between dancer which is one with other experience of different motion variation of. This matter happened caused by text meaning of different accompaniment music song text especially at middle Javanese song. This Research is more focused by about how audience and dancer mean song text in music dance related to dance motion expression. involved in Audience of complex situation that where they get